FACTORS AFFECTING CATCH RESULT MOTOR BOAT FISHERMAN IN MEUKEK DISTRICT SOUTH ACEH DISTRICT - Yusadi, Ratna; Thahir, Muhammad Agam (Asian Journal of Aquatic Sciences, 2022)
Meukek sub-district is one of communities located is south Aceh regency, which is located on the coast of the indian ocean because of the great potential and marine fisheries, so many people work as capture fisheries fishermen. The purpose of this research was to analyze the factors that influence of motorboat fishermen catch in meukek regenty. The research method was a quantitative descriptive with a survey approach. Total of samples was 34 respondents. The data analysis used was multiple linear regretion analysis. The result was factor of working capital (X1), labor (X2), fishing times (X3) and mileage (X4) has simultaneously significantly affected of the catches partially, only factor of labor (X2), mileage (X4) has significantly affected of the catchs, while factors of working capital (X1) and fishing times (X2) has not significantly effected of the catchs.